Determinants of waste separation behavior Tabriz, Iran: An application of the theory of planned behavior at health center - Babazadeh, Towhid; Ranjbaran, Soheila; Kouzekanani, Kamiar; Abedi Nerbin, Sanaz; Heizomi, Haleh; Ramazani, Mohammad Ebrahim (Frontiers in Environmental Science, 2023)
Background: Identifying factors that may influence waste separation behavior can lead to more effective waste separation, better recycling plans in a community, and more effective and efficient waste management interventions. The purpose of the survey was to identify the key factors behind such behavior. Methods: The scientific inquiry was cross-sectional in nature, took place in Tabriz, Iran, and employed multistage random sampling to recruit the study’s 360 participants. The data collection process took place between September 2018 and February 2019. A Theory of Planned Behavior-driven questionnaire was developed by the research team for the purpose of data collection. The structural equation modeling (SEM) approach was deployed for data analysis. Results: The structural equation modeling of the data showed the most important determinants of behavioral intention were perceived behavioral control (β = 0.39, p < 0.05), moral commitments (β = 0.19, p < 0.05), and perceived policy effectiveness (β = 0.12, p < 0.05). The strongest determinants of waste separation behavior were behavioral intention (β = 0.29, p < 0.05) and perceived behavioral control (β = 0.25, p < 0.05). In addition, age-group and gender differences were statistically related to waste separation behavior significantly (p < 0.05). Conclusion: Recycling investors and other stakeholders should focus on perceived behavioral control and intention in designing and implementing waste separation programs.